Resources in Finnish ECEC Centers - Confirming a Solid Ground for Future Readers - Aerila, Juli-Anna; Kauppinen, Merja (Pensa MultiMedia, 2025)
In this article, we investigate the literature resources in Finnish Early Childhood and Care(ECEC) groups. The results indicate that the quality and the number of books vary between groups and ECEC centres. In general, it seems that the personnel and administration ofECEC centres value children's literature differently: at best, there are high-quality and age-appropriate books for children. The literature in the daycare centres mostly concentrates on the most popular authors and book series in the timeline of decades as well as books aimed at socioemotional learning, which is one of the main aims in the Finnish Curriculum forEarly Childhood Education and Care (2018). Shortly, the books are broadly quite old anddo not meet with the diversity of children and their needs in ECEC groups.